Online grocery retailing in Germany: an explorative analysis - Seitz, Christian; Pokrivčák, Ján; Tóth, Marián; Plevný, Miroslav (Journal of Business Economics and Management, 2017)
The paper focuses on the German food retailing industry with its market characteristics and the status quo of online food retailing in Germany by analysing data from market research institutes and consumer direct questionnaire. The paper examines the consumers’ perceptions of online as well as offline grocery shopping. As a result, an online grocery model was created using PLS-SEM modelling. It illustrates all major success factors related to the consumer’s willingness to shop for groceries online in Germany. The main factors influencing the willingness to shop for groceries online are awareness of benefits, need for more convenience, and change of the lack of trust in the new distribution channel. We identified some consumer groups that are more open to online shopping as they benefit more from online grocery shopping. Especially working mothers and young professionals are the consumer groups with a high potential interest.